Geographical diversity of peer reviewers shapes author success - James M. Zumel Dumlao; Misha Teplitskiy (Proceedings of the National Academy of Sciences, 2025)
Scientific institutions like funding agencies and journals rely on peer reviewers to select among competing submissions. How does the geographical diversity of reviewers affect which authors are selected? If reviewers typically favor submissions from their own countries, but reviewers from only some countries are well represented in the reviewer pool, this can create a “geographical representation bias” favoring authors from those well-represented countries. Using administrative data on 204,718 submissions to 60 STEM journals from the Institute of Physics Publishing, we find support for representation bias. Reviewers from the same country as the corresponding author are 4.78 percentage points more likely to review positively compared to other reviewers of the same manuscript. Authors from the United States of America, China, and India are 8 to 9 times more likely to be evaluated by same-country reviewers compared to less-represented countries with similar incomes. Furthermore, an instrumental variables analysis of an anonymization policy shock shows that anonymizing submissions does not significantly reduce same-country homophily. Thus, investments in reviewer diversification may be necessary to mitigate the structural advantage of authors from major science-producing countries and avoid blind spots in collective knowledge.